1993
DOI: 10.1007/bf02374500
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular structure and function in proteinuric Type 2 (non-insulin-dependent) diabetic patients

Abstract: Glomerular ultrastructure was examined in a series of 20 Type 2 (non-insulin-dependent) diabetic patients with proteinuria. Reference was made to data previously obtained in non-diabetic kidney donors and in Type 1 (insulin-dependent) diabetic patients with similar degrees of proteinuria. The Type 2 diabetic patients demonstrated the changes which characterize the diabetic glomerulopathy seen in Type 1 diabetic patients: basement membrane thickening, and increase in the mesangium and mesangial matrix expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
87
5
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(106 citation statements)
references
References 31 publications
12
87
5
2
Order By: Relevance
“…However, we have previously shown that type 1 diabetic patients with clinical proteinuria and long duration (24-26 years) had larger glomeruli than proteinuric patients of shorter diabetes duration (14-16 years) [27]. In type 2 diabetic patients the time of onset of diabetes is often unknown, but Østerby et al demonstrated large glomeruli in type 2 diabetic patients with known diabetes duration of only 7 years [4]. The type 2 diabetic patients in our study were re-biopsied after 2 years and there was no significant difference in glomerular volume from baseline to follow-up [34].…”
Section: Does Duration Of Diabetes Affect Glomerular Volume?mentioning
confidence: 93%
See 3 more Smart Citations
“…However, we have previously shown that type 1 diabetic patients with clinical proteinuria and long duration (24-26 years) had larger glomeruli than proteinuric patients of shorter diabetes duration (14-16 years) [27]. In type 2 diabetic patients the time of onset of diabetes is often unknown, but Østerby et al demonstrated large glomeruli in type 2 diabetic patients with known diabetes duration of only 7 years [4]. The type 2 diabetic patients in our study were re-biopsied after 2 years and there was no significant difference in glomerular volume from baseline to follow-up [34].…”
Section: Does Duration Of Diabetes Affect Glomerular Volume?mentioning
confidence: 93%
“…We and others have shown that structural-functional relationships are similar in type 1 and 2 diabetic patients with clinical proteinuria [4,11]. However, there is greater heterogeneity of structural lesions and GFR in both microalbuminuric and proteinuric type 2 diabetic patients [4,8,12,13].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Indeed, most of the early descriptions were in mixed populations of diabetic patients as insulin was the only available treatment [11][12][13]. More recently, studies at the light and electron microscope level in carefully defined IDDM and NIDDM patients with nephropathy have failed to show any consistent differences [14].…”
Section: Esrd In Niddm: Microangiopathy Alone?mentioning
confidence: 99%